Virtual Helicopter Landing Platform (V-HELP) - Mustapa , Maria (Universiti Teknologi Petronas, 2004)
The research project focused on how virtual reality (VR) could create a non-immersive environment and improve in increasing safety awareness at offshore platform. The main problem is the typical training talk usually use video and audio presentation which cannot provide the walkthrough movement. The aim of this project is to develop and design Virtual Helicopter Landing Platform (V-HELP) application which allows users to explore the virtual platform environment. The objectives of this project are to design and develop helicopter landing platform; to visualize movement and facilitate understanding in VR; and at the same time identify components and characteristics of the virtual environment for adequate realism. In completion the project, the framework used is based on part of the waterfall "modeling theory. The phases involved in the framework used for project development is the analysis phase, design and development phase, integration and testing phase and lastly evaluation phase. Developments tools have been used in the project are 3D Maya 5..0.1 and Macromedia Flash MX software. As a result from the evaluation conducted, shows that most of the evaluators are satisfied with the project. They think that the realism of the prototype can be improved in virtual environment through enhancement on chosen the suitable textures materials and enable user control during walkthrough. As a conclusion, the research project show that Virtual Environment are very useful and more effective for the offshore safety training compared to the conventional method.